Analysis of the Possibilities of Using Automatic Control Systems for Operating Gas Engines for a Chilled Water Production. Issue 1 (January 2021) - Kurdziel, F; Kalwar, A; Pytel, K; Gumula, S; Marikutsa, U; Korpyljov, D
Abstract: The publication presents the impact of using automatic control systems for operating gas engines aimed at a chilled water production. The purpose of the work is to analyse the possibilities of using automation systems to regulate gas flow. An important parameter of fuel supplied to gas engines used in the production of cold is its amount, which depends on the pressure. Unstable operation of gas distribution systems caused by an extensive network, many customers and operation of devices working with different loads causes improper, unpredictable operation of other devices working in the network. Uncertainty of fuel parameters results in unstable operation of gas engines, their load, and variable production of electricity, heat and cold. Ensuring proper and stable production is a key element of production processes. The concept of building a gas pressure regulation system based on its amount in the network will ensure the required, stable operation of gas engines and refrigeration units coupled with them, and thus provide a guarantee of production of generated media. The presented solution provides a solution to existing problems. The system is based on two dampers coupled to each other and controlled by an automation system controlled by a superior SCADA system.